2020
DOI: 10.1002/aoc.5698
|View full text |Cite
|
Sign up to set email alerts
|

L‐argininato copper(II) complexes in solution exert significant selective anticancer and antimicrobial activities

Abstract: A search for new drugs that overcome the multidrug resistance of microorganisms or are effective against cancer cells prompted us to investigate the binary and ternary Cu(II) complexes containing L-arginine, [CuCl(L-Arg)(phen)] Cl•2H 2 O (phen = 1,10-phenanthroline) (1) and [Cu(L-Arg) 2 (H 2 O)]C 2 O 4 •6H 2 O (2), for which crystal and molecular structures were characterized previously. In order to discuss the biological function, the complexes have been screened for their antitumor activity against A549 (hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Cisplatin can bind to the purine bases of DNA and is able to cause DNA damage that, in turn, can cause cancer cell apoptosis [ 3 ]. However, some adverse side effects, such as toxicity, allergy, gastrointestinal disorders and kidney problems, plus the lack of selectivity and acquired resistance to this compound [ 4 , 5 , 6 ], led investigators to explore more selective and less toxic substituents. During this endeavor, in the past few years a large number of new metal complexes have been synthetized.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin can bind to the purine bases of DNA and is able to cause DNA damage that, in turn, can cause cancer cell apoptosis [ 3 ]. However, some adverse side effects, such as toxicity, allergy, gastrointestinal disorders and kidney problems, plus the lack of selectivity and acquired resistance to this compound [ 4 , 5 , 6 ], led investigators to explore more selective and less toxic substituents. During this endeavor, in the past few years a large number of new metal complexes have been synthetized.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of introducing natural origin structural groups with known biological activity into the complex is very productive. Antimicrobial activity of copper arginate complexes 14a, 14b was confirmed [27]. These coordination compounds contain L-argi-nine (HL 14 ) as a co-ligand.…”
Section: N-donor Ligandsmentioning
confidence: 83%
“…N,O-DONOR LIGANDS Publication [27] is one of works by Polish researchers devoted to study the structure and biological activity of copper complexes containing amino acids as ligands. The idea of introducing natural origin structural groups with known biological activity into the complex is very productive.…”
Section: N-donor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon suggested that these compounds may act as prodrugs having significant potential towards various cancer cell types [111]. Among the copper(II) complexes, a group with L−arginine (L−Arg; [Cu(L−Arg)2](NO3)2 and [Cu(L−Arg)(B)Cl]Cl⋅2.5H2O complexes (B = heterocyclic base)) was a remarkable idea for potential anticancer drugs [112,113]. Moreover, these compounds exhibited interesting It was proven that some of these inorganic compounds are able to interact with deoxyribonucleic acid molecules by releasing their ligands, leading to Cu(II)/Cu(I) redox processes that initiate the formation of reactive oxygen species (ROS) in vivo, especially hydroxyl radicals [110,111].…”
Section: Respiratory System Diseases Spike (S) Proteinmentioning
confidence: 99%